Contrarreforma psiquiátrica : o modelo hospitalocêntrico nas políticas públicas em saúde mental no Rio Grande do Sul - Souza, Vinícius Rauber e (2012)
The work adresses the process of psychiatric reform in Rio Grande do Sul. It focuses in the psychiatric counter-reform, with the return to the hospital-centered model centered on internation and on care in general hospitals to the mental health policies in place of the psychosocial model, based on outpatient and community treatment. It seeks to scan the conflicts, the disputes, the resources used by the groups, the main types of capital in the field, the current configuration, the participation of those involved in public debates and your main strategies and mechanisms of action. It emphasizes the formation of alliances and coalitions in the field of mental health in Rio Grande do Sul. The analysis focuses on groups that resist to the psychiatric reform, topic that remains largely untouched by the academic literature, examines their relationships and their role in the political arena in mental health. The empirical research, that has supported the work, was done from the observation of public debates and events on mental health, interviews with the agents in the field and from the reading of minutes of meetings, newspapers, blogs, theses and dissertations on the subject. We conclude that the model of mental health care for psychosocial base has been losing ground in public policy in recent years for the hospital-centered model, which has established itself as the dominant paradigm in the field of mental health mainly from the crack epidemic